PENYELESAIAN SENGKETA KEPEGAWAIAN AKIBAT TERKENA SANKSI BAGI PEGAWAI NEGERI SIPIL - Yadnya, I Made Adi Sucipta; Pemayun, Cok Istri Anom; Suardita, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012), 2012)
Public Servants have a very important role as a servant to hold the elements of thestateapparatus of government and development in order to achieve the purpose of thestate. Theexistence of a decision or lack of reasonable policy or self harm Servants,certainlypsychologically able to influence, disrupt, and prevent concentration in carryingout his duties asa Public Servant. Employment disputes as far as possible within the scopeof the work unit intansiissuing disciplinary decisions of moderate and severe levels in theform of dismissal with respectnot his own request and not with respect as Civil Servants(hereinafter abbreviated PNS) by thehead coach or official personnel both at central andlocal levels. Dispute among Civil Servants inthe presence of a decision or lack ofreasonable policies or adverse Servant can inhibitconcentration in duties as officers of theState. The formulation of the problem posed is whetherthe cause of employment disputesand legal actions that can be taken how civil servants due tothe imposition of sanctionsagainst him.
Keywords: Disputes, Sanctions, Civil servants and The Administrative Court